INFLUENCE OF GREEN TRANSFORMATIONAL LEADERSHIP ON ENVIRONMENTAL PERFORMANCE THROUGH ENVIRONMENTAL KNOWLEDGE SHARING AND GREEN ORGANIZATIONAL CULTURE IN SURABAYA STATE UNIVERSITIES - Sakti Noor Rachmat Ar-Ghaffar; Akhmad Fauzi; Muhadjir Anwar (RADJA PUBLIKA, 2025)
The increasing severity of environmental problems requires higher education institutions to play an active role in implementing sustainable policies, one of which is Green Transformational Leadership (GTL). This study aims to analyze the effect of GTL on environmental performance (EP) based on student perceptions at state universities in Surabaya, with a focus on the mediating roles of environmental knowledge sharing (EKS) and green organizational culture (GOC). The study employs a quantitative, explanatory research approach. Data were collected via questionnaires from 179 students and analyzed using the partial least squares structural equation modeling (PLS-SEM) method to test the direct and indirect effects of the variables. The results showed that GTL contributes directly to EP, and then EKS mediates the influence of GTL on EP. GOC also mediates the influence of GTL on EP. Therefore, it is necessary to strengthen the role of GTL in higher education, as well as improve organizational culture and collaboration in sharing environmental knowledge, to support sustainable EP.